Allergen management in the food industry - Boye, Joyce I.; Godefroy, Samuel Benrejeb (Wiley, 2010)
"This book comprehensively addresses the sources of allergenic contaminants in foods, their fate during processing, and the specific measures that need to be taken to minimize their occurrence in foods. The book provides up-to-date information on the nine major allergens (as well as other emerging allergens) and practical guidelines on how these allergens can be identified and controlled during production and processing. Starting with an introduction to food allergens, the book follows with sections on food allergen management during production and processing, guidelines for the processing of specific allergen-free foods, techniques for hypo-allergenization and allergen detection, and allergen-free certification"- Resumé vydavatele
Keywords: potravinářství; alergie na potraviny; food industry and trade; food allergy; elektronické knihy; sborníky; electronic books; papers of several authors